WEIGHT REDUCTION OF STEEL PASSENGER CARS - Myamlin, S. V.; Yahoda, P. O.; Dedaeva, T. O.; Shkarbov, O. O. (Science and Transport Progress, 2006)
The method of decline of weight of basket of passenger carriage is developed. A mathematical model is created, calculations are executed, some results are resulted.